Exploring the online presence of food SMEs: a study on configurations and determinants in the north-east of Italy - Francesca Checchinato; Vladi Finotto; Christine Mauracher (Cogent Business & Management, 2024)
This study investigates SMEs' online presence and sheds light on the different digital marketing approaches of firms in the food sector. An original analytic framework is developed to perform a fine-grained analysis of the various configurations of online presence in a sample of 520 SMEs in the north-east of Italy. A cluster analysis of the empirical data related to firms' online presence allowed the recognition of three configurations: pragmatists, laggards, and unfocused. The cluster analysis allows us to propose that the development of an online presence is far from being a unidirectional process that fits all organisations; it rather depends on a variety of organisational, strategic, and supply-chain related factors. To better illuminate these determinants and their influence on explaining the observed configurations, the study proposes the results of interviews with entrepreneurs and managers in a subset of firms from the sample. Qualitative evidence points to the importance of controlled and low-cost experiments, the integration of young talents in the marketing function of the firm, the existence of an explicit marketing strategy in the organisation, and the interaction between dedicated employees and external providers of digital services.
Keywords: 650; Digital marketing; social media; social media marketing; digital presence; sMes; cluster analysis